Dataset: Nitrous oxide cycling in the Western Arctic Ocean from stable isotopic and concentration data during the Seventh Chinese Arctic Research Expedition (CHINARE) (7/19/16 to 9/9/16) ... - Bourbonnais, Annie; Altabet, Mark; Li, Yangjie (NSF Arctic Data Center, 2021)
Nitrous oxide is a potent greenhouse gas in the troposphere and an ozone-depleting substance in the stratosphere, yet its sources and sinks in the ocean are neither well-quantified nor well understood. Nitrous oxide is both produced and consumed by microbial processes; it is produced by different processes dependent upon the amount of oxygen present locally. High nitrous oxide saturations were recently observed in productive shallow Arctic shelf waters. The primary goal of this dataset is to evaluate nitrous oxide cycling in the Western Arctic Ocean from its concentrations, stable isotopes and isotopomers. The project will use isotopic and isotopomer measurements from both shelf and offshore waters to constrain estimates of nitrous oxide cycling in the Arctic. The data will be used to evaluate 1) the pathways of nitrous oxide production from either nitrification following organic matter decomposition in the water column or coupled nitrification-denitrification in the sediments and 2) how these processes ...